Aesthetic and expressive characteristics in the works of Jean Dubuffet (Al-Academy, 2023)
The research presented the tagged (aesthetic and expressive characteristics in the works of Jean Dubuffet), so the research objective was: to know the aesthetic and expressive characteristics in the works of (Jean Dubuffet), and the research included four chapters. The aim of the research, the limits of the research, and the definition of terms. The second chapter included four topics. The first topic presented the aesthetic essence and style, while the second topic dealt with expressionism: approaches in concept and meaning.While the third topic was preoccupied with presenting the aesthetic and expressiveness in the drawings of modernity and beyond, while the fourth topic dealt with: Jean Dubuffet and the experience of raw art. The third chapter was devoted to research procedures. In order to achieve the aim of the research, a number of results were reached in the fourth chapter, including:1- The aesthetic and expressive characteristics were manifested in all samples of the sample, including: instinct / emotion / mood / violence / madness / vulgarity / ugliness / distortion / rebellion / audacity / research, experimentation and innovation.2- The value of his works and his artistic experience was embodied through his interest and fondness for raw art derived from the products of children, insane, and prisoners. He considered primitive and popular art as a source of aesthetic value for him at the expense of all aesthetic and philosophical concepts, as shown in Model (1 and 3).